Strain relaxation and stress-driven interdiffusion in InAsInGaAsInP nanowires - Nieto, L.; Bortoleto, J. R R [UNESP]; Cotta, M. A.; Magalhães-Paniago, R.; Gutírrez, H. R. (AIP Publishing, 2007)
The authors have investigated strain relaxation in InAsInGaAsInP nanowires (NW's). Transmission electron microscopy images show an additional stress field attributed to compositional modulation in the ternary layer, which disrupts NW formation and drives Ga interdiffusion into InAs, according to grazing incidence x-Ray diffraction under anomalous scattering conditions. The strain profile along the NW, however, is not significantly affected when interdiffusion is considered. Results show that the InAs NW energetic stability is preserved with the introduction of ternary buffer layer in the structure. © 2007 American Institute of Physics.
Keywords: Diffusion; Indium compounds; Strain relaxation; Transmission electron microscopy; X ray diffraction; Compositional modulation; Stress driven interdiffusion; Stress fields; Ternary layers; Nanowires